Leishmania major: effect of repeated passages through sandfly vectors or murine hosts - Sádlová, J; Svobodová, M; Volf, P (Annals of tropical medicine and parasitology, 1999)
Virulence for BALB/c mice, infectivity for Phlebotomus papatasi, haemagglutination activity and expression of metacyclic lipophosphoglycan (LPG) were studied in four strains of Leishmania major (LV561, FV1, L119 and Neal) and various lines of the LV561 strain. Attenuated line LV561/AV was passaged five times through sandflies or mice and the resulting lines (AVS5 and AVM5, respectively) and two of the earlier sandfly passages (AVS1 and AVS2) were used for further study. The highly virulent line LV561/V served as a control. Virulence for mice was not regained during passaging of LV561/AV in sandflies or mice (none of the mice infected with AVM5, AVS1, AVS2 or AVS5 displayed overt lesions) and the success rate in cultivating parasites, from lymph-node samples from inoculated mice, was not significantly higher for any of these lines than for the original line (LV561/AV). However, AVM5 and AVS5 developed better than LV561/AV in P. papatasi and the intensity and localisation of their infections were similar to those of the virulent control. In smears of the infected guts of P. papatasi, the AVS5 parasites resembled the virulent line (LV561/V) morphologically whereas the AVM5 parasites were similar to the avirulent LV561/AV. Haemagglutination activity increased as a result of passaging, the most pronounced difference being observed in AVM5, which had 60-fold higher activity than LV561/AV. Expression of metacyclic LPG was not increased by passaging. The proportion of forms reacting positively with 3F12 antibodies was high (about 17%) in the virulent LV561/V but low (2%-3%) in the avirulent lines LV561/AV, AVS5 and AVM5. A defect in LPG is not, however, likely to be the only reason for the avirulence observed, as the avirulent lines of LV561 still produced about 10 times as many metacyclic promastigotes as the strain L119, which caused delayed lesions in mice.
Keywords: ženské pohlaví; myši inbrední BALB C; Female; hmyz - vektory; Animals; Glycosphingolipids; Leishmania major; Male; virulence; Mice, Inbred BALB C; glykosfingolipidy; mužské pohlaví; myši; Insect Vectors; Virulence; zvířata; Psychodidae; Mice